Rethinking social inquiry : diverse tools, shared standards - Brady, Henry E.; Collier, David, 1942- (Rowman & Littlefield Publishers, 2010)
With innovative new chapters on process tracing, regression analysis, and natural experiments, the second edition of Rethinking Social Inquiry further extends the reach of this path-breaking book. The original debate with King, Keohane, and Verba--now updated--remains central to the volume, and the new material illuminates evolving discussions of essential methodological tools. Thus, process tracing is often invoked as fundamental to qualitative analysis, but is rarely applied with precision. Pitfalls of regression analysis are sometimes noted, but often are inadequately examined. And the complex assumptions and trade-offs of natural experiments are poorly understood. The second edition extends the methodological horizon through exploring these critical tools. A distinctive feature of this edition is the online placement of four chapters from the prior edition, all focused on the dialogue with King, Keohane, and Verba. Also posted online are exercises for teaching process tracing.